The application of infrared thermo-camera in testing of silicon-based thin-film solar cells. Issue 1771 (13th May 2015) - Han, Meiying; Zhu, Yonghong; Xie，Xiangqi Luo, Xishun; Tang, Liangneng; Tan, Yiping
ABSTRACT: Thermo-camera is employed here to analyze kinds of quality abnormal and improve production process during manufacture procedure of silicon-based thin-film solar modules. It shows that thermo-camera device can help engineers to solve problem of production line quickly and accurately, and save the manpower and financial resources at the same time.